Post-concussion return to play and return to school guidelines for children and youth: a scoping methodology. (June 2015) - DeMatteo, Carol; McCauley, Dayle; Stazyk, Kathy; Harper, Jessica; Adamich, John; Randall, Sarah; Missiuna, Cheryl
Abstract Purpose: The objective of this study was to identify and describe management strategies to ensure safe return to activity (RTA) and return to school (RTS) of children with mild traumatic brain injury (MTBI) and determine whether they are evidence-based. Methods: A scoping methodology was conducted using research published between 1990 and 2013, gray literature and clinical expertise. Once the data had been charted, an expert panel of physicians and clinicians was consulted to inform and validate study findings. An analytical and thematic framework was used to examine the study findings. Results: A total of 400 potentially relevant published articles, 100 websites and 24 iPad Applications were found. Ten articles and three web-based resources met inclusion criteria and were included in the final review. Nine articles recommended a more conservative approach to RTA, as well as identified a step-wise or severity-oriented approach. General recommendations were also found regarding safe RTS. One study recommended a stepwise RTS protocol for children. Conclusions: This scoping methodology determined that the most comprehensive guidelines for management are focused on adults. Evidence concerning prolonged recovery patterns in children and the impact of concussion on the developing brain suggests that pediatric-specific guidelines are needed for RTA and RTS after MTBI/concussion. Implications for Rehabilitation Although concussion in children is an increasing concern, it has been determined that the most comprehensive guidelines for management are focused on adults. These guidelines are primarily consensus-based and are not proven fact through quality research. Evidence concerning prolonged recovery patterns in youth and the impact of concussion on the developing brain suggest that pediatric guidelines should be more conservative than for adults. Therefore, pediatric-specific guidelines need to be developed for return to activity and return to school after MTBI/concussion.